2021
DOI: 10.18502/ijph.v50i5.6120
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Comparison of Separate or Combinatorial Effects of Potential Inhibitors of the SARS-CoV-2 Binding Site of ACE2

Abstract: Background: The COVID-19 is a pandemic viral infection with a high morbidity rate, leading to many worldwide deaths since the end of 2019. The RBD (Receptor Binding Domain) of SARS-CoV-2 through its spike utilizes several host molecules to enter host cells. One of the most important ones is the angiotensin-converting enzyme 2 (ACE2), an enzyme normally engaged in renin angiotensin pathway and is responsible for hypertension regulation. As different articles have analyzed separate compounds which can bind ACE2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…For the hACE2/S-RBD of the Delta variant, Song et al [ 51 ] found that baicalein interacts with Asp30, Lys26, Leu29, Asn33, Glu96, Pro389, Gln388, Ala387, Thr92, Val93, and Asn90 residues. Shakhsi-Niaei et al [ 52 ] reported that baicalin is a candidate that is able to occupy hACE2 and inhibit viral RBD binding, i.e., baicalin is a strong inhibitor of the SARS-CoV-2 binding site of ACE2. The results of this molecular simulation study showed that baicalin interacts with the active site through three hydrogen bonds with A396, E208, and D206.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the hACE2/S-RBD of the Delta variant, Song et al [ 51 ] found that baicalein interacts with Asp30, Lys26, Leu29, Asn33, Glu96, Pro389, Gln388, Ala387, Thr92, Val93, and Asn90 residues. Shakhsi-Niaei et al [ 52 ] reported that baicalin is a candidate that is able to occupy hACE2 and inhibit viral RBD binding, i.e., baicalin is a strong inhibitor of the SARS-CoV-2 binding site of ACE2. The results of this molecular simulation study showed that baicalin interacts with the active site through three hydrogen bonds with A396, E208, and D206.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this molecular simulation study showed that baicalin interacts with the active site through three hydrogen bonds with A396, E208, and D206. Many scientists are currently studying the possibility of developing molecules, for example, those based on baicalein and baicalin from S. baicalensis , as effective antiviral drugs [ 24 , 33 , 50 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In silico , multiple components containing in KT and SSKKS were also identified as candidates to have potential inhibitory activities against SARS-CoV-2. The crude drugs with such potential activities include Bupleurum root, Scutellaria root, Glycyrrhiza ( Hejazi et al, 2021 ; Shakhsi-Niaei et al, 2021 ; Yu et al, 2021 ), Ginger ( Teng et al, 2021 ; Zubair et al, 2021 . ), Pueraria root ( Pan et al, 2020 ), Ephedra herb ( Lv et al, 2021 ), and Cinnamon bark ( Prasanth et al, 2021 ; Husain et al, 2022 .).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, several recent study on G. glabra in combination with standard therapies demonstrated significantly reduction of hospitalization rate and occurrence of COVID-19 symptoms ( Armanini et al, 2020 ; Zhong et al, 2020 ; Gajewski et al, 2021 ; Li et al, 2021a ; 2021b ). Recently, several targets have been identified with the possible interaction of medicinal plants included liquorice a hopeful therapeutic for future drug ( Bandyopadhyay et al, 2021 ; Shakhsi-Niaei et al, 2021 ; Tsai et al, 2021 ). Glycyrrhizin was studied well in past and found to be the most active molecule for inhibition of replication of the SARS-associated virus and can be utilized for treatment of SARS -associated coronavirus ( Cinatl et al, 2003 ).…”
Section: Potential Health Benefit Of G Glabra As Anti-inflammatory Antiviral and Immunomodulatory Agentsmentioning
confidence: 99%